2017
DOI: 10.1093/nc/nix013
|View full text |Cite
|
Sign up to set email alerts
|

fMRI-based decoding of reward effects in binocular rivalry

Abstract: Binocular rivalry is a phenomenon where the simultaneous presentation of two different stimuli to the two eyes leads to alternating perception of the two stimuli. The temporary dominance of one stimulus over the other is influenced by several factors. Here, we studied the influence of reward on binocular rivalry dynamics and its neural representation in visual cortex. Orthogonal rotating grating stimuli were shown continuously, while monetary reward was given during the conscious perception of one stimulus but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In Chopin and Mamassian’s study, observers were unaware of the task relevance of the stimulus and nonetheless a profound effect on its dominance was found. Taken together with the results of Wilbertz et al. (2017), this indicates that task-relevance effects are unlikely to be mediated by the implicit reward of better task performance.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In Chopin and Mamassian’s study, observers were unaware of the task relevance of the stimulus and nonetheless a profound effect on its dominance was found. Taken together with the results of Wilbertz et al. (2017), this indicates that task-relevance effects are unlikely to be mediated by the implicit reward of better task performance.…”
Section: Discussionsupporting
confidence: 61%
“…This is most evident in the case of reward, where stimuli that are associated with positive outcome (reward) are enhanced in dominance and those associated with negative outcome (punishment) are reduced in dominance (Marx & Einhäuser, 2015; Wilbertz et al., 2014). Interestingly, such reward effects have not been found when observers were unaware of the stimulus-reward contingency (Wilbertz et al., 2017), which suggests that a (meta-cognitive) awareness of a stimulus-outcome association is critical for reward-based effects on multistable perception. In this respect, the effects of perceptual difficulty, which already occur—albeit weaker—when no task is to be conducted with the stimuli, may be conceptually distinct from effects of motivational value.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate techniques such as representational similarity analysis have provided insight into the fine spatial patterns representing stimulus information in the brain ( Haxby et al, 2001 ; Kriegeskorte et al, 2008 ). Here, we applied a different form of multivariate analysis, classification in the temporal domain, to reveal individualized percept-specific patterns in neural activity (see also Reichert et al, 2014 ; Wilbertz et al, 2017 for classification of bistable visual perception).…”
Section: Discussionmentioning
confidence: 99%
“…In a second experiment that utilized the same design but a financial loss of 10 Cent instead of gain, an increase in dominance durations for the non-punished percept relative to the punished percept was found. Interestingly, in a subsequent study that combined a similar button press task with functional magnetic resonance imaging of neural rivalry correlates as an objective online measure of perception, Wilbertz et al (2017) were unable to confirm this finding. Marx and Einhäuser (2015) found that rewarding a percept led to a similar increase in dominance as attending it, but at a constant level of attention reward still modulated dominance.…”
Section: Introductionmentioning
confidence: 86%